2013
DOI: 10.1186/1753-6561-7-s7-s2
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualization of molecular findings by mining gene annotations

Abstract: BackgroundThe Gene Ontology (GO) is an ontology representing molecular biology concepts related to genes and their products. Current annotations from the GO Consortium tend to be highly specific, and contemporary genome-scale studies often return a long list of genes of potential interest, such as genes in a cancer tumor that are differentially expressed than those found in normal tissue. It is therefore a challenging task to reveal, at a conceptual level, the major functional themes in which genes are involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The overall framework of this study is shown in Fig 2, which consists of the following steps to search for a set of mutually exclusive driver SGAs that affect a common signal: 1) We first identified differentially expressed genes from each tumor, and then grouped genes into non-disjoint functional sets according to their Gene Ontology [18] (GO) annotation using the methods previous developed by our group [19][20][21], such that functions of the genes in a set are coherently related to each other and are summarized by a GO term from the Biological Process Domain of the GO (Fig 2A). 2) After selecting the differentially expressed genes annotated with a common GO term across tumors, we constructed a bipartite graph consisting of tumors on one side and the genes on the other side, and we then searched for a densely connected subgraph (Fig 2B).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The overall framework of this study is shown in Fig 2, which consists of the following steps to search for a set of mutually exclusive driver SGAs that affect a common signal: 1) We first identified differentially expressed genes from each tumor, and then grouped genes into non-disjoint functional sets according to their Gene Ontology [18] (GO) annotation using the methods previous developed by our group [19][20][21], such that functions of the genes in a set are coherently related to each other and are summarized by a GO term from the Biological Process Domain of the GO (Fig 2A). 2) After selecting the differentially expressed genes annotated with a common GO term across tumors, we constructed a bipartite graph consisting of tumors on one side and the genes on the other side, and we then searched for a densely connected subgraph (Fig 2B).…”
Section: Methodsmentioning
confidence: 99%
“…To find such modules among the cancer tumors, we employed a knowledge-driven data mining approach, developed in our previous studies [19][20][21], which consists of two major procedures: 1) identifying functionally coherent gene subsets among the differentially expressed genes in each tumor, such that each gene subset is annotated by a GO term that summarizes the function of the genes; and 2) further identifying the gene subsets that are differentially expressed in multiple Overall scheme. A) Use GO structure and semantic information to categorize differentially expressed genes in each tumor into functionally coherent subgroups.…”
Section: Identifying Gene Modules As Signal-response Unitsmentioning
confidence: 99%
See 3 more Smart Citations